An evaluation process for natural ventilation using a scenario-based multi-criteria and multi-interaction analysis - Duygu Utkucu; Hatice Sözer (Energy Reports, 2020)
This study examines natural ventilation with respect to human thermal comfort conditions using a scenario-based, multi-criteria, and multi-interaction analysis. The proposed methodology evaluates the design development process in terms of decisions on building physics and building geometry during the early design stages to maximize human thermal comfort conditions and reduce cooling load requirements. The methodology integrates a detailed three-dimensional (3D) building and computational fluid dynamics (CFD) modeling within a building information modeling (BIM) platform during the design development stage, which is developed and structured to optimize the evaluation process. The operational characteristics of the building in respect of windows and shutters have important effects on natural ventilation, which in turn influences thermal comfort, and cooling load. Thus, the multi-interaction analysis of natural ventilation is considered with operational schemes of enveloping that are integrated into a 3D model of the building, which is further transformed to a CFD model. Then, four scenarios using a manually operated building opening are created using the BIM platform. Thus, multi-interactions are achieved by developing a 3D-building model, that not only include the building's functions and physical specifications but also incorporates the envelope's thermal capacity coupled with openings that have various operational scenarios for natural ventilation. The results show that the correlation between the air temperature and velocity can provide a comfort zone and decrease the cooling load for energy consumption. The numerical results for one scenario 2 show that if the temperature and velocity values are increased together, human sensation as predicted mean vote (PMV) ranges from 0 to 2, which is considered tolerable for summer comfort, whilst the cooling load is reduced by almost 3%.
Keywords: 330; BIM; CFD analysis; Design with natural ventilation; Optimization of design process